INTERNATIONAL COOPERATION IN COUNTERING MONEY LAUNDERING (Journal of actual problems of jurisprudence, 2024)
Money laundering has a transnational impact on international and regional security, as it is associated with dangerous crimes of an international nature. Laundering of illegal proceeds increases the volume of the shadow economy, negatively affecting the economic security of the state. Combating the legalization of criminal proceeds requires a collective response to existing threats within the framework of international cooperation, since the fight against this phenomenon is impossible solely at the national level. The purpose of the study is a comparative legal analysis of international anti-money laundering instruments, identification of problems and arguments for their solutions, analysis and implementation of international anti-money laundering standards in the Republic of Kazakhstan. The methodological basis of the study was a systematic approach to the study of conventional and institutional instruments for combating money laundering. The authors identified issues of correlation between the law enforcement practice of the Republic of Kazakhstan and international standards as a separate vector of research. The conducted research allowed us to draw a conclusion about the multi-level nature of international legal regulation and the formulation of proposals for unification, innovation and codification of international norms on combating the legalization of illegal income. The practical significance of the work is aimed at eliminating the problems of law enforcement practice, due to the insufficient tools of international cooperation in combating the legalization of illegally obtained income.Keywords: money laundering, international cooperation, money laundering, anti-money laundering, Financial Action Task Force, Eurasian Group on Combating Money Laundering and the Financing of Terrorism, 40+2 FATF recommendations, Basel Committee, terrorist financing.